CONSIDERING THE IMPLEMENTATION OF CHILDREN’S CHARACTER EDUCATION INCULCATION IN INDONESIA AND JAPAN - Arif Syamsurrijal (Pedir Research Institut, 2021)
Young generation is an asset for every country. Therefore, assuring and maintaining their quality are important thing to do and it is becoming responsibility for schools, parents, also government. Due to the rapid development of technology, many negative side effects appear such as addiction to online games, high number of crime case, drugs, terrorism and others. In order to counter those side effects, Indonesia has supported the implementation of character education in schools. Besides, another country such as Japan also implemented this education. This short writing intended to compare the implementation character education in both countries so that the insights of each could complete one another. Keywords: Indonesia, Japan, Character Education, Young Generation.